2017
DOI: 10.18632/oncotarget.21121
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 is a major mediator of doxorubicin chemoresistance in breast cancer cells through a cullin4A-MDR1 pathway

Abstract: Development of chemoresistance is a persistent problem during cancer treatment. Long non-coding RNAs (LncRNAs) are currently emerging as an integral functional component of the human genome and as critical regulators of cancer development and progression. In the present study, we investigated the role and molecular mechanism of H19 lncRNA in chemoresistance development by using doxorubicin (Dox) resistance in breast cancer cells as a model system. H19 lncRNA expression was significantly increased in anthracycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…Subsequent experimental analysis identified several lncRNAs which act as oncogenes or tumor suppressors in this type of cancer (38)(39)(40). Moreover, the overexpression or downregulation of lncRNAs has been used as a breast cancer biomarker, aiming to improve detection of this disease at an early stage or predict the sensitivity of the patients to chemotherapy (41)(42)(43). The present study demonstrated that lncRNA small nucleolar RNA host gene 1 (SNHG1) was overexpressed in breast cancer and that it promoted breast cancer cell growth, cell cycle and migration, suggesting its oncogenic role.…”
Section: Discussionmentioning
confidence: 62%
“…Subsequent experimental analysis identified several lncRNAs which act as oncogenes or tumor suppressors in this type of cancer (38)(39)(40). Moreover, the overexpression or downregulation of lncRNAs has been used as a breast cancer biomarker, aiming to improve detection of this disease at an early stage or predict the sensitivity of the patients to chemotherapy (41)(42)(43). The present study demonstrated that lncRNA small nucleolar RNA host gene 1 (SNHG1) was overexpressed in breast cancer and that it promoted breast cancer cell growth, cell cycle and migration, suggesting its oncogenic role.…”
Section: Discussionmentioning
confidence: 62%
“…Next, we detected several known lncRNAs involved in drug resistance in K562 and K562/ADM cells by qRT-PCR, such as HOTAIR [28], PVT1 [29], H19 [10], MALAT1 [30], UCA1 [11], CCAL [31], ANRIL [32], MEG3 [33] and FENDRR [12]. Interestingly, we found that FENDRR was mostly downregulated in K562/ADM cells compared with that in K562 cells ( Fig.…”
Section: Lncrna Fendrr Level Was Downregulated In Adriamycin-resistanmentioning
confidence: 86%
“…Long noncoding RNA (lncRNA) is a class of nonprotein coding transcripts longer than 200 nucleotides, which have been shown to play crucial roles in drug resistance [9]. For example lncRNA H19 plays a leading role through H19-CUL4A-ABCB1 pathway in breast cancer chemoresistance [10]. And lncRNA UCA1 can compete with MDR1 mRNA 3 0 UTR (untranslated region) for miR-16 in imatinib-resistant CML [11].…”
mentioning
confidence: 99%
“…H19 also affects drug resistance in breast cancer via the H19-CUL4A-ABCB1/MDR1 pathway. Experimental results showed that knocking out H19 significantly increased MDR1 and MRP4 in Dox-resistant breast cancer cells, which identified the role of H19 in breast cancer resistance [16].…”
Section: Regulating Drug Effluxmentioning
confidence: 88%